Developing a community of practice to promote the use of biological control in the integrated management of Prosopis in South Africa - Van Staden, Gretha (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Prosopis spp. are non-native species present in the arid parts of southern Africa. These trees originated in the Americas and were first introduced as a source of fodder, shade, and wood, but have become invasive, negatively impacting local biodiversity, and disrupting the delivery of ecosystem services. Some species of Prosopis hybridise freely, complicating identification and subsequent control. The control of Prosopis in the Northern Cape Province of South Africa is still contentious, because of the perceived benefits to some landowners. The effectiveness of biological control agents to control the spread of Prosopis has been quantified, more damaging agents have been considered in recent years because of the continued increase in Prosopis density. Research into the establishment of a Community of Practice (CoP) to address the differences in perceptions regarding the control of Prosopis in the Northern Cape Province is considered an appropriate starting point to conceptualise the challenges to the successful integrated management of Prosopis. As farmers are the main stakeholders involved with Prosopis control, understanding the role of farmers and the functioning of farming enterprises in the Northern Cape is imperative for the development of both a CoP as well as the appropriate management of Prosopis. To foster engagement with as many stakeholders as possible, workshops dealing with biological control as part on an integrated approach to the control of Prosopis were held in towns in the Northern Cape Province: Groblershoop, Brandvlei, Kenhardt, Upington, Prieska and Williston. Some of the main concerns of the landusers include the host specificity of the released biocontrol agents, as well as increased transparency and communication. This is especially in regards to the research on present and future biological control agents that will possibly improve the perceptions of stakeholders. The mechanical harvesting and use of biomass as a control method was supported, especially where farmers were removing Prosopis from their properties, leaving large amounts of biomass in the veld. Continued research into Prosopis in the Northern Cape needs to consider the possibility of secondary invasions, especially in areas where native bush encroachment is already a concern. The impact of clearing in terms of natural grazing and animal improvement needs to be quantified, to conceptualise the importance of maintaining better veld quality versus using Prosopis for fodder. Biological control targeting not only the reproductive output of the trees, but also the standing biomass has support from the majority of the land users in the Northern Cape Province following these workshops and this study shows the importance of a socio-ecological approach to the control of landscape scale invasion.
Keywords: Mesquite -- South Africa Northern Cape; Community of practice; Stakeholder participation; Mesquite Control; Invasive plants Biological control; Prosopis